PENGARUH HUKUM PERSAINGAN USAHA TERHADAP PLATFORM BISNIS DIGITAL TANTANGAN DAN ADAPTASI REGULASI DI INDONESIA - Ahmad Nurafendi; Pandri Zulfikar; Eduardo Retno; Ronny Erlando; Imam Fathwa (Berajah Journal, 2026)
The development of digital business platforms in Indonesia has fundamentally changed market structure and business competition dynamics. Digital platforms such as e-commerce, ride-hailing, and fintech bring efficiency and innovation, but also create risks of anti-competitive practices that are not fully accommodated in the existing legal framework. Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (Competition Law), which has been in force for more than two decades, faces significant challenges in regulating the digital economy characterized by dual roles of platforms, network effects, and two-sided market dominance. This study aims to analyze the influence of competition law on digital business platforms in Indonesia, identify law enforcement challenges, and formulate necessary regulatory adaptations. The method used is normative legal research with statutory, conceptual, and comparative approaches. The results indicate that the Competition Law has not accommodated digital economy dynamics, particularly regarding dual roles of platforms as both marketplace providers and business operators, data-based anti-competitive practices, algorithmic discrimination, and two-sided market dominance. Furthermore, the non-adoption of extraterritoriality principles limits the authority of the Commission for the Supervision of Business Competition (KPPU) in enforcing the law against foreign platforms. This study recommends modernization of the Competition Law, strengthening of KPPU capacity, and establishment of specific digital platform regulations to create a healthy and innovative competition ecosystem.